Growth-inhibitory effects of winged bean (Psophocarpus tetragonolobus) proteinase inhibitors on two problematic lepidopteran pests - GUPTA, G P; BIRAH, AJANTA; RANI, SEEMA (The Indian Journal of Agricultural Sciences, 2011)
A laboratory study conducted during 2004–05 showed that winged bean [Psophocarpus tetragonolobus (L.) DC] proteinase inhibitors inhibited the growth and development of Helicoverpa armigera (Hübner) and Spodoptera litura (Fab.). It affected the larval and pupal survival and adult emergence in a dose-dependent manner. Larval-pupal intermediates and malformed adults were also observed. At higher dose of winged bean proteinase inhibitors (4.5 trypsin inhibitor units/g of diet), 44.1% of H. armigera and 50% of S. litura could only survive. There was no fecundity at this dose, however, at its lower dose less fecundity was observed, but hatching could not take place in both the test insects, thereby there was no subsequent generation. The growth and developmental indices reduced from 5.46 (control) to 3.53 (proteinase inhibitors fed) and 2.84 to 1.36 in H. armigera, and their values in S. litura reduced from 5.55 to 5.0 and 3.0 to 1.44 respectively.